Nutrition Counseling by Medical Students at a Student-Run Free Clinic Using Goal-Setting and the MyPlate Method - Thuy-An Tran; Nancy Yang; Natalie Davis; Katherine Arden; David Skovran; Brijen Shah; David Thomas; Yasmin Meah (Journal of Student-Run Clinics, 2017)
Background: Lifestyle counseling in the primary care setting has been shown to have significant health outcome benefits for patients with chronic diseases like diabetes, obesity, and cardiovascular disease. General physicians often do not provide adequate lifestyle and nutrition counseling due to time constraints or lack of knowledge and training. In order to increase access to nutrition counseling in a low-resource setting and to increase physician comfort in counseling patients, we designed an intervention in which medical students conducted nutrition counseling using goal-setting and teaching MyPlate.Methods: This study was conducted at the East Harlem Health Outreach Partnership, a student-run, physician-supervised free clinic that serves uninsured adults. Student clinicians used a standardized script to provide nutrition counseling to patients, and patients’ pre- and post-intervention knowledge of MyPlate and nutrition goals were recorded. Results: Fifty-seven patients and 36 students participated in the intervention with a significant increase in patients’ knowledge of MyPlate and health goals. Conclusions: We posit that this simple intervention can be implemented in primary care clinics, especially those in which medical students rotate.